PERSEPSI SISWA DAN GURU PAMONG TERHADAP PELAKSANAAN PEMBELAJARAN SOSIOLOGI OLEH MAHASISWA PPL DI SMA SWASTA KOTA PADANG TAHUN AJARAN 2013/2014 - RAMADHONA, AULIA - (Pendidikan Sosiologi, 2014)
This study aimed to determine the perception of Students and Teachers AdvisorImplementation PPL Student Learning in Sociology by Padang Private High School2013/2014 school year.This study used quantitative and descriptive approach percentage. In this study theauthors used according to Gestalt theory of social psychology. Gestalt theory explains thefirst adjustment is to get a response and appropriate responses. Determination of informantsconducted by purposive sampling technique. The informants in this study amounted to over190 people in 3 high school students and 6 Padang Private tutor teachers. Each high schoolstudent Semen Padang numbered 62 people and 2 tutors teachers, high school studentsKartika 1-5 Padang numbered 81 people and 2 teachers and tutors high school students PGRI3 amounted to 47 people and 2 teachers tutor. The data collected in the form of primary dataand secondary dataFrom the research it can be concluded that: 1) students perception of theimplementation of learning sociology by PPL students in 3 private schools each indicator ispre-learning, open learning, mastery of teaching materials, approaches / learning strategies,use of learning resources / media learning, learning that trigger and maintain studentengagement, use a good language, and learning outcomes assessment process, which coverless well categorized on a frequent choice. 2) Perception of teachers on the implementation oflearning sociology tutors by students in high school PPL Private desert town in accordancewith each of the indicators the formulation of learning objectives, selection and organizationof teaching materials, the selection of learning resources / learning media, the appearance infront of the class, teaching methods, assessment learning outcomes are categorized quite wellon frequent choice.